Endogenous myoglobin expression in mouse models of mammary carcinoma reduces hypoxia and metastasis in PyMT mice - Mostafa A. Aboouf; Julia Armbruster; Franco Guscetti; Markus Thiersch; Andreas Boss; Axel Gödecke; Sandra Winning; Claudia Padberg; Joachim Fandrey; Glen Kristiansen; Anne Bicker; Thomas Hankeln; et al. (Scientific Reports, 2023)
Abstract Myoglobin (MB) is expressed in different cancer types and may act as a tumor suppressor in breast cancer. The mechanisms by which basal MB expression level impacts murine mammary tumorigenesis are unclear. We investigated how MB expression in breast cancer influences proliferation, metastasis, tumor hypoxia, and chemotherapy treatment in vivo. We crossed PyMT and WapCreTrp53flox mammary cancer mouse models that differed in tumor grade/type and onset of mammary carcinoma with MB knockout mice. The loss of MB in WapCre;Trp53flox mice did not affect tumor development and progression. On the other hand, loss of MB decreased tumor growth and increased tissue hypoxia as well as the number of lung metastases in PyMT mice. Furthermore, Doxorubicin therapy prevented the stronger metastatic propensity of MB-deficient tumors in PyMT mice. This suggests that, although MB expression predicts improved prognosis in breast cancer patients, MB-deficient tumors may still respond well to first-line therapies. We propose that determining the expression level of MB in malignant breast cancer biopsies will improve tumor stratification, outcome prediction, and personalized therapy in cancer patients.